Behavioral antecedents of coopetition: A synthesis and measurement scale. Issue 1 (February 2020) - Czakon, Wojciech; Klimas, Patrycja; Mariani, Marcello
Abstract: This study taps into managers' perceptions of coopetition antecedents to better understand why firms adopt coopetition. By analyzing and synthesizing findings from systematic reviews of coopetition literature we integrate knowledge on coopetition antecedents. We develop and validate a scale measuring behavioral coopetition antecedents: strategic rationale and coopetition mindset. Based on a random sample of 368 Polish tourism firms, we run exploratory and confirmatory factor analyses to find that antecedents used in coopetition literature converge into two latent, behavioral constructs. Our data substantiate the view that coopetition is an intentional strategy, driven by a strategic rationale. Managers are found to pursue coopetition in order to reach clearly defined benefits with fitting partners. Moreover, three elements are found to converge in the coopetitive mindset latent construct: orientation to cooperation, trust, and experience in coopetition. We contribute to the methodological advancement of measurement instruments with applicability potential in future research examining the behavioral antecedents of coopetition. We also advance the behavioral stream of research in strategy by empirically identifying the connection between rational and behavioral antecedents of firms' coopetitive strategic behavior.